A face do caos: a crônica de guerra em Guimarães Rosa - BARBOSA, Waldete Freitas (Universidade Federal do Pará, 2018)
João Guimarães Rosa’s anthology, Ave, palavra, was posthumously published in 1970. It is a compilation of 54 texts described by the author as a “miscellany”, a collection of travel notes, journals, poems, short stories, chronicles, events, poetic reports and meditations, all of them, associated to the thematic variety of some texts in verse with a philosophical approach. They formed his collaboration during the 20 years he wrote for Brazilian newspapers and magazines. This Master’s dissertation aims to study João Guimarães Rosa’s chronicle based on his 1970 book, focusing on the problem of classification of texts in their testimony nature. For this study the following chronicles were selected: “O mau humor de Wotan” (Wotan’s Bad Humor) (02.29.1948 — Correio da Manhã Newspaper); “A senhora dos segredos” (The Lady of Secrets) (12.06.1952 — Correio da Manhã); “Homem, intentada viagem” (Man, The Intended Trip) (02.18.1961 — O Globo Newspaper); “A velha” (The Old Lady) (06.03.1961 — O Globo). Reading and interpretation of the mentioned chronicles address the historical context of the 20th Century, during World War II. Considering the studies done by Massaud Moisés (1978) ,Afrânio Coutinho (1997), Antonio Candido (1997) and Jorge de Sá (2005), it was understood that this textual genre teaches us to live intimately with the word, considering that everything is life and a reason for reflection, which is perceived throughout the reading of the Ave, palavra author’s chronicles, for the writer, who was born in the State of Minas Gerais, does not lose sight of the fact that reality is not merely duplicated, but recreated. The paper is based on studies formulated by Hans Robert Jauss (1979), which focus the primacy of hermeneutic centered on the reader, clarifying, on one side, the current process that concretizes the effect and meaning of the text for the contemporary reader and, on the other side, reconstructs the historical process by which the text is received and interpreted by readers of different eras.